IMPLIKASI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 18/PUU-XVII/2019 TERHADAP HAK EKSEKUTORIAL JAMINAN FIDUSIA - Safitri Saraswati; Pranoto Pranoto (Jurnal Privat Law, 2025)
This article aims to knowing the implications of the Constitutional Court Decision Number 18/PUU-XVII/2019 on the executorial rights of fiduciary guarantees. This research is normative legal research or literature law research with a statute approach and a case approach. The nature of this research uses analytical descriptive, namely a method that serves to describe a picture of the object under study through the data that has been collected. The data used are secondary data. The technique used in the collection of legal materials in this study is to collecting or collect legal material and download legal material. This study uses the method of analysis of legal materials by interpretation.Based on this research, it is found that the existence of the Constitutional Court Decision Number 18/ PUU-XVII/2019 implications for the existence and executorial rights of fiduciary guarantees; debtors become more arbitrarily in using collateral and creditors will think again in providing loans with fiduciary guarantees.